Investigation of Performance of Soil-Cement Pile in Support of Foundation Systems for High-Rise Buildings - Dao Huu Do; Tuan A. Pham (Civil Engineering Journal, 2018)
This paper presents the experimental study of Soil-Cement Pile (SCpile) by wet mixing method in sandy soils, with the typical project at An Trung Complex apartment, Da Nang city, Vietnam. With the characteristic of soil layers is sandy soil, the strength of laboratory stabilized soils with the amount of cement from 150¸300 kg/m3 was determined. Simultaneously, the authors also performed the experiments of 20 test piles collected from the site which has cement content about 280 kg/m3 and the unconfined compressive strength qu= (4.5-6.0) MPa. After that, a full-scale model static axial compressive load tests of two single piles and a group of four piles with diameter 800 mm and 12 m length were also conducted. The experiment results show that the bearing capacity of every single pile is 1.200 kN with settlement 6.93 mm and the group of four CSpiles is 3.200 kN with settlement 5.03 mm. The results presented in the paper illustrate that SCpile is the suitable solution for foundation construction process with low cost and saving time for high rise buildings. The result shows a capable application of soil cement piles for support of high-rise buildings.